PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN OBJEK DAYA TARIK WISATA BENDUNGAN SUNGAI PAKU KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Tessa Rahmadani; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is conducted on sungai paku village kampar kiri district kampar regency. The aim of this research is to identify the society's participations on tourist attraction object of sungai paku dam and to analyze the factors that influencing the society's participations.the method of this research is descriptive quantitative method, with total 76 respondents of sungai paku villagers that chosen by using simple random sampling. The finding of this research shows that society's participation there is classified low. There are two factors that influencing their participation on tourist attraction development, first is the internal factor that divided into three categories which are age level, educational level and personal income level. The second is external factor that is consist ofthe influence of the driving actor, the existence of village rules,then access and control of resources. Keywords: participation, development